Beirut massive blast explosion: A unique injury pattern of the wounded population. Issue 2 (February 2023) - Yammine, Kaissar; Daher, Jimmy; Otayek, Joeffroy; Jardaly, Achraf; Mansour, Jad; Boulos, Karl; Alam, Anthony El; Ghanimeh, Joe; Abou Orm, Ghady; Berberi, Mary; Daccache, Elio; Helou, Mariana; et al.
Highlights: The massive Beirut blast of August 4, 2020 resulted in an extraordinary gigantic pressure wave. The devastating majority of injuries were due to glass shrapnel. Unlike bomb blasts, a unique injury pattern was observed where most injuries were located in the head and upper extremities. Abstract: Introduction: On August 4, 2020, a massive explosion of a warehouse holding 2, 700 metric tons of ammonium nitrate took place in the port of Beirut, Lebanon. This incident, which is considered as one of the largest industrial disasters lead to the death of at least 220 people and more than 6000 injuries. Hospitals near the blast were damaged significantly which made it difficult to treat injured patients. The objective of this study is to report the epidemiology and characteristics of the injuries and their initial management that could be useful for healthcare workers and policymakers in case of a similar massive accident in the future. Materials and methods: A retrospective study was conducted. All charts of patients admitted to the emergency room and outpatient clinics on the day of the blast and during the following 2 weeks were thoroughly reviewed. Due to initial chaos during triage, direct phone contact with patients was utilized in certain situations to confirm their identity or for further information. All acute injuries were recorded based on the region, severity, degree of emergency, initial and later management, type of injured organs, and surgical procedures. Results: A total of 159 patients presented to our facility. 153 patients presented to the ER on the same day of the blast. The mean age was 47.07 years and around 60% of the patients were males ( n = 93). Most of the patients presented either from zone 1 ( n = 67, 42%) or zone 3 ( n = 68, 43%). The majority of injuries were secondary injuries due to glass ( n = 131, 82.3%), with the head (34%) and upper extremities (31.2%) being most commonly affected. A total of 94 patients (62.6%) underwent a type of imaging and 64 patients (40.2%) had at least one surgery performed during their hospitalization in which 71% of the surgeries being related to the limbs. Conclusion: This study demonstrated a unique injury pattern due to this type of blast. Injuries were mostly due to glass shrapnel. Contrary to bomb blasts, most injuries were located in the head and upper extremities rather than on the lower extremities.